HUBUNGAN KINERJA PENGURUS TERHADAP KEPUASAN ANGGOTA PADA KOPERASI KHIZAINUL KHOIR DESA ALAHAIR KABUPATEN KEPULAUAN MERANTI - Zuliya Zuliya; Makhdalena Makhdalena; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to see the relationship between the performance of cooperative administrators and the satisfaction of cooperative members. The population of this study were members of the Khizainul Khoir cooperative which amounted to 30 people and all were studied. The type of data from this study is primary data sourced from cooperative members using a questionnaire. Data analysis techniques from this study use product moment with the help of SPSS. The results of the study show that the performance of cooperative administrators is positively related to the satisfaction of members of the Khizainul Khoir cooperative at 0.407.Keywords: Managemen, Performance, Member, Satisfaction